The strategic Israel stages to Separation of South Sudan from the Republic of Sudan - Odeh, Ibrahim Youssef Hammad (Journal of Humanities & Social Sciences, 2024)
Since its inception, Israel has followed multiple methods to divide the Arab world to weaken it, and this is what happened in the Republic of Sudan when it was divided into two parts until the time of research. It used nine stages, beginning with the method of money ambassadors, which is intended for commercial cooperation, until it arrived at supporting the movements and turning them against the ruling regime, and even attacking them. Direct military control of Sudanese lands, and in the end blackmailing the government into accepting secession. This research aims to uncover these plans and means that Israel is following to divide the Arabs and their homelands, so that attention must be paid to every small and large thing. There is no trade, no embassy, and no cooperation except behind it lurking and planning for division. The researcher used the descriptive analytical method, where the focus was on describing plans followed by Israel to separate southern Sudan from its north. He also used the historical method, which provides a presentation on the relationship of Sudanese governments with Israel and its policies towards Sudan. The study came up with results, the most important of which is that Israel seeks to divide the Arab countries, because of its A clear role in the secession of South Sudan, and cooperation in any form, economic, diplomatic, commercial, political, is a door for the enemy to enter through to attack this country. Israel used methods and means of financial support and interference in unions and parties inside and outside Sudan. It did not hesitate to invest in any strategic point to separate the south. The researcher used the historical method to narrate the facts and also used the descriptive analytical method to describe and analyze Israel’s intervention and how to invest it. This research resulted in the following: The first method of intervention is commercial and the end is blackmail to submit to the orders of Israeli intelligence and services.